2019
DOI: 10.1111/ans.15103
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation score is a prognostic marker after curative resection in gastric cancer

Abstract: Background The systemic inflammation score (SIS), as calculated from preoperative serum albumin level and lymphocyte‐to‐monocyte ratio, has been demonstrated to be a prognostic marker in cancer. The present study intended to investigate the prognostic role of SIS in gastric cancer patients after curative gastrectomy in comparison with other prognostic markers. Methods Preoperative SIS was retrospectively calculated in patients who underwent curative gastrectomy between 2007 and 2011 in Fudan University Shangha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…NPS indicates both inflammatory and nutritional states, along with SIS. Typically, SIS, which is based on the preoperative serum Alb concentration and LMR, is considered as a novel prognostic indicator for GC and ESCC (37,38). The results of our study suggested that SIS was related to the prognosis for AEJ patients; But when we use the SIS to predict RFS, the HR of SIS=1 is similar to the HR of SIS=2, and there is no dose responsibility.…”
Section: A B Figure 2 | (A)mentioning
confidence: 71%
“…NPS indicates both inflammatory and nutritional states, along with SIS. Typically, SIS, which is based on the preoperative serum Alb concentration and LMR, is considered as a novel prognostic indicator for GC and ESCC (37,38). The results of our study suggested that SIS was related to the prognosis for AEJ patients; But when we use the SIS to predict RFS, the HR of SIS=1 is similar to the HR of SIS=2, and there is no dose responsibility.…”
Section: A B Figure 2 | (A)mentioning
confidence: 71%
“…The serum albumin level and white blood cell count were obtained before surgery in the previous studies of SIS 79. In the present study, the serum albumin level and white blood cell count obtained before adjuvant chemoradiotherapy were used to evaluate the role of SIS for AEs and survival in locally advanced rectal cancer patients treated with TME followed by adjuvant chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the study including 441 clear-cell renal cell carcinoma patients undergoing nephrectomy, SIS was firstly reported to be associated with tumor behaviors and OS after adjusting for traditional clinicopathological features and other markers of systemic inflammation responses 7. The higher SIS score was also associated with poorer OS and DFS in gastric cancer patients after curative gastrectomy 9. In the study of evaluating the prognostic impact of the SIS in colorectal cancer patients after curative resection, 161 (22.1%) patients with rectal cancer who did not receive neoadjuvant chemoradiotherapy or radiation therapy were included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory, SIS, combining LMR and albumin, could better reflect disease change and predict survival outcome. And this assumption has been reported to predict prognosis in several cancer types, including clear cell renal cell carcinoma, gastric cancer and colorectal cancer (23)(24)(25). There are no previous reports regarding the use of SIS in breast cancer.…”
Section: Introductionmentioning
confidence: 96%